Second polar body incorporation into a blastomere results in 46,XX/69,XXX mixoploidy. - Müller, U (1993)
A case of 46,XX/69,XXX mixoploidy is described. The patient had a normal 46,XX diploid karyotype in lymphocytes but a triploid 69,XXX cell line in most of her fibroblasts. In order to learn more about the underlying mechanism resulting in mixoploidy, we studied short tandem repeat polymorphisms (STRPs) in lymphocyte DNA of the patient's parents and in both lymphocyte and fibroblast DNA of the proband. The findings showed maternal origin of the supernumerary chromosome complement and are best explained by second polar body incorporation into a blastomere.